Loss of two-pore channel 2 enhances CD8+ T cell cytotoxicity and directly impairs tumour growth via MAPK axis in HCC - Ouologuem, Lina; Kübler, Anna; Ouologuem, Sarah; Hadzic, Amar; Stöckl, Jan B.; Siciliano, Anna Chiara; Forciniti, Stefania; Nigro, Salvatore; Iuele, Helena; Onesto, Valentina; Nguyen, Anny; Matzek, Dana; et al. (Frontiers in Immunology, 2025)
IntroductionHepatocellular carcinoma (HCC) remains a major global health challenge, characterised by limited therapeutic options and high mortality rates. Despite significant progress in systemic and immune-based therapies, many patients develop resistance or fail to respond, highlighting the need for new molecular targets. Lysosomal ion channels have recently emerged as important regulators of cancer biology; however, their involvement in tumour–immune interactions is still poorly understood.MethodsTo investigate the role of the endolysosomal two-pore channel 2 (TPC2) in HCC, we employed genetic and pharmacological approaches, including TPC2 knockout (KO) and pharmacological inhibition using SG094. Functional analyses combining co-culture assays with CD8⁺ T cells, flow cytometry, and multi-omics profiling were conducted to assess the impact of TPC2 modulation on immune regulation, metabolic reprogramming, and intracellular signalling. Combination studies using SG094 and the immune checkpoint inhibitor Nivolumab were performed in vitro to evaluate synergistic effects.ResultsLoss or inhibition of TPC2 enhanced CD8⁺ T cell-mediated cytotoxicity by increasing MHC-I and reducing PD-L1 expression both in vitro and in vivo. Combined treatment with SG094 and Nivolumab further augmented CD8⁺ T cell cytotoxicity compared with single-agent immune checkpoint blockade. Multi-omics analysis revealed that TPC2 KO disrupted amino acid metabolism, glycolysis, and protein translation, resulting in reduced ERK1/2 expression and impaired MAPK signalling. These metabolic and signalling alterations were associated with decreased tumour proliferation and increased MHC-I surface expression.DiscussionOur findings identify TPC2 as a dual regulator of tumour-intrinsic signalling and immune evasion in HCC. By modulating oncogenic MAPK activity and antigen presentation pathways, TPC2 influences both cancer progression and responsiveness to immunotherapy. Targeting TPC2 therefore represents a promising strategy to enhance immune checkpoint inhibitor efficacy in hepatocellular carcinoma.